2020
DOI: 10.1299/jbse.20-00012
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and simulation of a single abrasive grain micro-grinding force and temperature of bone

Abstract: Grinding methods have been widely used in orthopedic surgery, which has high requirements for surface quality, grinding force and temperature control. It is necessary to explore the influence of micro-grinding parameters on the grinding force temperature from a microscopic perspective. This paper describes the micro structure, composition and thermodynamic properties of bone. From the perspective of the single abrasive grain, the single abrasive grain cutting model is established, and the single abrasive grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Because the interface strength between the bone and bone plate is relatively weak, it may lead to cracking during cutting. In bone cutting, the formation of bone milling debris is similar to that of unidirectional composites, which mainly depends on the cutting depth and osteon orientation [14], as shown in Figure 3.…”
Section: Preparation Of Bone Specimenmentioning
confidence: 98%
“…Because the interface strength between the bone and bone plate is relatively weak, it may lead to cracking during cutting. In bone cutting, the formation of bone milling debris is similar to that of unidirectional composites, which mainly depends on the cutting depth and osteon orientation [14], as shown in Figure 3.…”
Section: Preparation Of Bone Specimenmentioning
confidence: 98%
“…According to the grinding direction of the abrasive particles and the direction of the bone unit, the cutting modes can be divided into vertical direction, parallel direction, and cross direction. In our early research [13,14], it was found that the grinding temperature and grinding force in the vertical direction are the largest among the three cutting modes, followed by the cross direction, and the grinding temperature and grinding force in the parallel direction are the smallest. In order to explore the cooling and lubricating effect of coolant on bone grinding temperature, the grinding direction selected in FE simulation is the vertical direction with the largest grinding temperature shown in Figure 3(a).…”
Section: Fe Model Of Single Abrasive Bone Grindingmentioning
confidence: 99%